Method for efficiently preparing furfural through catalytic hydrolysis of cellulose
By using waste prepared carbon-based catalysts and aprotic polar compound solvents for cellulose hydrolysis, the problems of low yields in traditional methods and difficult to recover catalysts are solved, and high-efficiency and low-pollution preparation of furfural is achieved.
Patent Information
- Application Number
- CN202411277455.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Traditional cellulose hydrolysis to prepare furfural is low yield and the catalyst is difficult to separate and recover, resulting in high pollution and high economic costs.
Carbon-based materials are prepared by waste plastics/scrap rubber/scrap lignin and other wastes, and FeCl3 is loaded and acidified to obtain a solid acid catalyst. Cellulose hydrolysis is carried out in combination with aprotic polar compound solvent to achieve efficient preparation of furfural.
The yield and selectivity of furfural are improved, easy separation and recovery of catalysts are achieved, and pollution and economic costs of the hydrolysis process are reduced.
Smart Images

Figure CN119569686A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing furfural by catalytically and efficiently hydrolyzing cellulose, and belongs to the technical field of biomass hydrolysis and waste utilization. Background Art
[0002] Lignocellulose is widely present in nature. If used reasonably, lignocellulose can be used to prepare new fuels and high-value-added chemicals, especially the recycling of agricultural and forestry wastes, which can not only reduce the pressure of waste treatment, but also further obtain high-value-added products. On the other hand, wastes such as waste plastics / waste rubber / waste lignin are excellent carbon-based materials. Using these wastes to prepare carbon-based catalysts can turn waste into treasure and realize the resource utilization of solid waste. Therefore, the combined utilization of the above two types of wastes has broad application prospects.
[0003] Lignocellulosic raw materials are usually composed of three major components: cellulose, hemicellulose and lignin. The proportion of each of the three major components varies with the type of raw materials. Among them, cellulose accounts for the highest proportion (40%-60%) and is the most abundant natural polymer in the world. Furfural (C5H4O2) is a high-value platform compound. It is reported that it is the only biomass-derived organic compound that can replace crude oil-based organic matter used in industry. More than 1,600 chemical products can be directly or indirectly derived from furfural as a raw material, which are widely used in medicine, pesticides, resins, daily chemicals, textiles and petrochemical industries. Hemicellulose is mainly composed of pentose, which is relatively low in molecular weight and degree of polymerization, and is easily hydrolyzed into furfural; cellulose is a polysaccharide compound composed of hexose connected by β-1,4 glycosidic bonds. The selectivity of cellulose for furfural during hydrolysis is usually 30-40%. The present invention will propose a method for efficiently converting cellulose into furfural. Summary of the invention
[0004] Purpose of the invention:
[0005] A method for efficiently preparing furfural by catalytic hydrolysis of cellulose, the method mainly comprising the preparation of a hydrolysis catalyst and an optimized hydrolysis method based on the catalyst, using waste plastics / waste rubber / waste lignin and other waste materials as raw materials to prepare carbon-based materials, further loading FeCl3 and acidifying to obtain a solid acid catalyst, and combining with a non-protonic polar compound solvent to achieve efficient conversion of cellulose to furfural.
[0006] Since traditional homogeneous catalysts have the disadvantages of being difficult to separate subsequent products from the catalyst, inconvenient to recycle, and causing high pollution, a new solid hydrolysis catalyst proposed in the present invention will further overcome the above disadvantages and achieve a low-pollution, high-efficiency furfural production process.
[0007] Technical solution:
[0008] The present application provides a method for efficiently preparing furfural by catalytic hydrolysis of cellulose, the method comprising the preparation of a hydrolysis catalyst and an efficient hydrolysis method, comprising the following steps:
[0009] Step 1: Weigh 2g-10g of carbon-based raw materials and place them in a tube furnace. Blow off with N2, set the tube furnace to 500°C, and carbonize them in a N2 atmosphere. Mix the carbonized black solid powder and metal chloride, add them to deionized water and stir, and then stir them magnetically in a water bath. After magnetic stirring, filter and dry to obtain a carbon-based solid loaded with metal salts.
[0010] Step 2: Mix the dried carbon-based solid loaded with metal salts with sulfuric acid in a polytetrafluoroethylene reactor, and place the reactor in an oven for acidification for 12 hours to obtain a black solid-liquid mixture;
[0011] Step 3: After the reaction kettle is cooled to 25° C., the black solid-liquid mixture is washed with deionized water, and the black solid substance is obtained by suction filtration, and calcined to obtain a metal halide-carbon-based solid acid hydrolysis catalyst;
[0012] Step 4: weigh the hydrolysis catalyst metal halide-carbon-based solid acid obtained in step 3 and the cellulose raw material, mix them and place them in a hydrothermal reactor, add a solvent and mix them evenly;
[0013] Step 5: Set the reaction temperature of the hydrothermal reactor and keep it warm. After the reaction is completed and the temperature drops to 25°C, take out the solid-liquid mixture and filter it. The filtrate obtained is rich in furfural.
[0014] The present invention has the following beneficial effects:
[0015] Beneficial effects: Compared with the prior art, the present invention has the following advantages:
[0016] (1) The present invention provides a method for efficiently preparing furfural by catalytic hydrolysis of cellulose, wherein the hydrolysis catalyst (solid) has the advantages of being easy to separate the subsequent product from the catalyst and convenient to recycle compared with the current technology. Based on this, the reuse efficiency of the catalyst can be effectively improved and the pollution to water during the hydrolysis process can be reduced.
[0017] (2) In the prior art, the yield of furfural prepared by cellulose hydrolysis is 30-40%, while the reaction medium γ-valerolactone, γ-butyrolactone and cyclopentane sulfone used in the present application are typical non-protonic polar solvents. The solvent molecules affect the reaction kinetics by changing the stability of the protonated transition state of the intermediate substance to accelerate the acid-catalyzed cellulose conversion process. The non-protonic polar solvent can dissolve the intermediates, by-products and polymers formed during the catalytic or non-catalytic reaction, eliminate them to prevent them from participating in the furfural degradation reaction, reduce the deactivation of the catalyst caused by the deposition of carbon-containing compounds on the surface, and thus slow down the degradation rate of furfural, enhance the stability of furfural in the system, and ultimately improve the yield and selectivity of furfural.
[0018] (3) In the hydrolysis catalyst prepared in the present invention, the Lewis acid sites required for the hydrolysis reaction are provided by metal salt loading, and the Lewis acid sites in the hydrolysis reaction are provided by acidification. acid sites, so the prepared hydrolysis catalyst can have both Lewis acid and Acid sites; L acid can effectively promote the isomerization of glucose into aldose-ketose, and then B acid is used to catalyze its dehydration to generate furfural. The catalytic system formed by the combination of the catalyst and the hydrolysis solvent has a synergistic effect, which greatly promotes the yield of furfural when cellulose is used as the hydrolysis raw material. In addition, the selection of specific metal chlorides for loading can also use chloride ions to further provide catalytic active sites on the catalyst surface, thereby realizing a trinity (three different catalytic active sites of -Fe, -SO3H, and -Cl) hydrolysis catalyst, thereby effectively improving the utilization value of cellulose raw materials, and the furfural yield can reach 66%.
[0019] (4) The present invention can use agricultural waste rich in cellulose as raw material, and use carbonized combustible solid waste as a catalyst to prepare a substrate. Through a series of optimized preparation processes, the conversion efficiency of cellulose to prepare furfural by efficient hydrolysis can be effectively improved; applying this technology to industrial production can effectively reduce economic costs, achieve cost reduction and efficiency improvement, and has a good economic and applicability prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The application provides a flow chart of a method for efficiently preparing furfural by catalytic hydrolysis of cellulose;
[0021] Figure 2 Furfural yield diagram in the liquid product of the examples of the present application. DETAILED DESCRIPTION
[0022] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.
[0023] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0024] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0025] An embodiment of the present application provides a method for efficiently preparing furfural by catalytic hydrolysis of cellulose, the method comprising preparing a hydrolysis catalyst and a highly efficient hydrolysis method, comprising the following steps:
[0026] Step 1: Weigh 2g-10g of carbon-based raw materials and place them in a tube furnace. Blow off with N2, set the tube furnace to 500°C, and carbonize them in a N2 atmosphere. Mix the carbonized black solid powder and metal chloride, add them to deionized water and stir, and then stir them magnetically in a water bath. After magnetic stirring, filter and dry to obtain a carbon-based solid loaded with metal salts.
[0027] Step 2: Mix the dried carbon-based solid loaded with metal salts with sulfuric acid in a polytetrafluoroethylene reactor, and place the reactor in an oven for acidification for 12 hours to obtain a black solid-liquid mixture;
[0028] Step 3: After the reaction kettle is cooled to 25° C., the black solid-liquid mixture is washed with deionized water, and the black solid substance is obtained by suction filtration, and calcined to obtain a metal halide-carbon-based solid acid hydrolysis catalyst;
[0029] Step 4: weigh the metal halide-carbon-based solid acid hydrolysis catalyst obtained in step 3 and the cellulose raw material, mix them and place them in a hydrothermal reactor, add a solvent and mix them evenly;
[0030] Step 5: Set the reaction temperature of the hydrothermal reactor and keep it warm. After the reaction is completed and the temperature drops to 25°C, take out the solid-liquid mixture and filter it. The filtrate obtained is rich in furfural.
[0031] In one embodiment, the carbon-based feedstock includes combustible solid waste.
[0032] In one embodiment, the combustible solid waste includes waste plastics, waste rubber and waste lignin.
[0033] In one embodiment, the metal chloride in step 1 is ferric chloride, wherein the amount of the metal chloride is: the molar ratio of the metal element to the cellulose is x:1, wherein 0≤x≤1.
[0034] In one embodiment, in step 1, the heating rate of the tube furnace is 15°C / min-25°C / min; the carbonization time in the N2 atmosphere is 2h-4h; and the temperature of the water bath is 25°C-40°C.
[0035] In one embodiment, in step 2, the reaction kettle is placed in an oven for acidification for 10 hours to 12 hours.
[0036] In one embodiment, in step 3, the black solid material obtained by filtration is calcined at 500° C. to 600° C. for 3 h to 6 h.
[0037] In one embodiment, in step 3, the black solid material obtained by filtration is calcined at 500° C. for 3 hours.
[0038] In one embodiment, in step 4, the mass ratio of the catalyst to the cellulose is m 催化剂 :m 纤维素 =x:1, where 0.5≤x≤4.
[0039] In one embodiment, the solvent added in step 4 is an aprotic polar compound.
[0040] In one embodiment, the solvent added in step 4 includes γ-valerolactone, γ-butyrolactone and sulfolane.
[0041] In one embodiment, in step 4, the solid-liquid ratio of the raw material to the solvent during the reaction is 1:10-20.
[0042] In one embodiment, in step 5, the reaction temperature of the hydrothermal reactor is set to 150°C-210°C, the heating rate is 10°C / min-20°C / min, and the insulation time is 30min-180min.
[0043] One embodiment of the present application provides a method for efficiently preparing furfural by catalytic hydrolysis of cellulose, the method comprising a hydrolysis catalyst preparation and an efficient hydrolysis method, selecting combustible solid waste as a substrate, using metal chloride as a loading agent, and preparing a solid hydrolysis catalyst with excellent catalytic performance by acidification and over-impregnation. Thanks to the excellent acid sites of the catalyst and the further optimization and regulation of the acid sites by metal loading, the optimal Lewis acid and can be adjusted by changing the loading amount of metal elements, acidification temperature and time during the preparation process. A catalyst with an optimal balance point in the ratio of acid to furfural is prepared, thereby obtaining a hydrolysis catalyst with high furfural selectivity, which has the advantages of high furfural selectivity and easy recovery; the hydrolysis solvent and hydrolysis conditions are further optimized and designed, and the catalyst and the non-proton polar compound hydrolysis solvent are combined to synergistically greatly increase the furfural yield during cellulose hydrolysis, completing the integrated design of the catalyst from preparation to hydrolysis to efficiently prepare furfural, and ultimately achieving a high conversion rate for preparing furfural from cellulose as a raw material.
[0044] An embodiment of the present application provides a method for preparing a hydrolysis catalyst, comprising the following steps:
[0045] Step 1: Weigh a certain mass of combustible solid waste and place it in a tubular furnace. After N2 is blown off for a certain period of time, set the tubular furnace to 500°C at an appropriate heating rate, and carbonize it in a N2 atmosphere. Add the carbonized black solid powder and an appropriate amount of metal chloride into deionized water and stir to mix them evenly. Then, magnetic stirring is performed in a water bath at a certain temperature, and then the carbon-based solid loaded with metal salts is filtered and dried;
[0046] Step 2: After completing step 1, mix the dried solid with a certain amount of sulfuric acid in a polytetrafluoroethylene reactor, and place the reactor in an oven for acidification for 12 hours;
[0047] Step 3: After the reaction kettle cools to room temperature, wash the black solid-liquid mixture with deionized water until the filtrate is neutral. Filter the black solid substance, calcine it at 500°C for 3h, and the resulting substance is a metal halide-carbon-based solid acid catalyst;
[0048] Step 4: Weigh a certain mass of catalyst and cellulose raw material, mix them according to a certain mass ratio and place them in a hydrothermal reactor, add a certain amount of solvent according to a certain solid-liquid ratio and mix them evenly.
[0049] Step 5: Set the reaction temperature of the hydrothermal reactor to a certain value, and heat it at an appropriate heating rate. After reaching the set temperature, keep it warm for a certain time. After the reaction is completed and cooled to room temperature, take out the solid-liquid mixture and filter it. The filtrate obtained is rich in furfural.
[0050] In one embodiment of the present application, the molar ratio of the Fe element to the cellulose when loaded is x:1, wherein 0≤x≤1. In one embodiment, the molar ratio of the Fe element to the cellulose when loaded is preferably 1:1.
[0051] In one embodiment of the present application, the mass ratio of catalyst to cellulose is set to m catalyst : m cellulose = x: 1, 0.5≤x≤4. In one embodiment, the mass ratio of catalyst to cellulose is preferably set to x = 0.5.
[0052] In one embodiment of the present application, the specific organic solvent added is γ-valerolactone, γ-butyrolactone or cyclopentane sulfone, the reaction temperature of the hydrothermal reactor is set to 150-210°C, preferably 150°C, the heating rate is 10-20°C / min, preferably 15°C / min, and the insulation time is 30min-180min, preferably 60min.
[0053] Example 1 Carbonization of waste polyethylene plastic as a substrate for preparing catalysts for hydrolyzing cellulose to efficiently prepare furfural
[0054] Step 1: Weigh 2 g of waste polyethylene plastic and place it in a tubular furnace. After N2 stripping for a certain period of time, set the tubular furnace to 500°C at 20°C / min and perform carbonization in a N2 atmosphere. Add the carbonized black solid powder and an appropriate amount of ferric chloride (molar ratio 1:1) into 50 ml of deionized water and stir to mix them evenly. Stir magnetically in a 30°C water bath for 2 hours, then filter to obtain a carbon-based solid loaded with metal salts, and calcine at 550°C for 4 hours.
[0055] Step 2: After completing step 1, 0.5 g of the dried solid was mixed with 5 ml of sulfuric acid in a polytetrafluoroethylene reactor, and the reactor was placed in an oven at 180° C. for acidification for 12 h;
[0056] Step 3: After the reaction kettle cools to room temperature, wash the black solid-liquid mixture with deionized water until the filtrate is neutral. Filter the black solid substance, calcine it at 500°C for 3h, and the resulting substance is a metal halide-carbon-based solid acid catalyst;
[0057] Step 4: Mix the catalyst and the cellulose raw material in a mass ratio of 1:2 and add a certain amount of solvent (γ-valerolactone) to mix evenly;
[0058] Step 5: Add the solid-liquid mixture in step 1 to a high-pressure reactor, set the hydrolysis reaction temperature to 150°C, and heat at a rate of 15°C / min to maintain the high-efficiency hydrolysis at 150°C for 60 minutes; after the reaction kettle is cooled to room temperature, the solid-liquid mixture is filtered to retain the liquid product;
[0059] Step 6: The liquid product is further filtered, and 2.0 ml of the liquid product is measured and analyzed by gas chromatography-mass spectrometry GC / MS. The product component analysis is carried out against the NIST spectral library, and the furfural yield in the liquid product is calculated to be 66.5% based on the analysis data, see Figure 2 .
[0060] Example 2 Carbonization of waste lignin as a substrate for preparing catalyst for hydrolyzing cellulose to efficiently prepare furfural
[0061] Step 1: Weigh 2 g of waste polyethylene plastic and place it in a tubular furnace. After N2 stripping for a certain period of time, set the tubular furnace to 500°C at 20°C / min and perform carbonization in a N2 atmosphere. Add the carbonized black solid powder and an appropriate amount of ferric chloride (molar ratio 1:1) into 50 ml of deionized water and stir to mix them evenly. Stir magnetically in a 30°C water bath for 2 hours, then filter to obtain a carbon-based solid loaded with metal salts, and calcine at 550°C for 4 hours.
[0062] Step 2: After completing step 1, 0.5 g of the dried solid was mixed with 5 ml of sulfuric acid in a polytetrafluoroethylene reactor, and the reactor was placed in an oven at 180° C. for acidification for 12 h;
[0063] Step 3: After the reaction kettle cools to room temperature, wash the black solid-liquid mixture with deionized water until the filtrate is neutral. Filter the black solid substance, calcine it at 500°C for 3h, and the resulting substance is a metal halide-carbon-based solid acid catalyst;
[0064] Step 4: Mix the catalyst and the cellulose raw material in a mass ratio of 1:2 and add a certain amount of solvent (γ-butyrolactone) to mix evenly;
[0065] Step 5: Add the solid-liquid mixture in step 1 to a high-pressure reactor, set the hydrolysis reaction temperature to 180°C, and heat at a rate of 15°C / min to maintain at 180°C for 50 minutes to carry out efficient hydrolysis; after the reaction kettle is cooled to room temperature, the solid-liquid mixture is filtered to retain the liquid product;
[0066] Step 6: The liquid product is further filtered, and 2.0 ml of the liquid product is measured and analyzed by gas chromatography-mass spectrometry GC / MS. The product component analysis is carried out against the NIST spectral library, and the furfural in the liquid product is calculated based on the analysis data. 63.8%, see Figure 2 .
[0067] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for efficiently preparing furfural by catalytic hydrolysis of cellulose, characterized in that: The method comprises a hydrolysis catalyst preparation and an efficient hydrolysis method, comprising the following steps: Step 1: Weigh 2g-10g of carbon-based raw materials and place them in a tube furnace. Blow off with N2, set the tube furnace to 500°C, and carbonize them in a N2 atmosphere. Mix the carbonized black solid powder and metal chloride, add them to deionized water and stir, and then stir them magnetically in a water bath. After magnetic stirring, filter and dry to obtain a carbon-based solid loaded with metal salts. Step 2: Mix the dried carbon-based solid loaded with metal salts with sulfuric acid in a polytetrafluoroethylene reactor, and place the reactor in an oven for acidification for 12 hours to obtain a black solid-liquid mixture; Step 3: After the reaction kettle is cooled to 25° C., the black solid-liquid mixture is washed with deionized water, and the black solid substance is obtained by suction filtration, and calcined to obtain a metal halide-carbon-based solid acid hydrolysis catalyst; Step 4: weigh the metal halide-carbon-based solid acid hydrolysis catalyst obtained in step 3 and the cellulose raw material, mix them and place them in a hydrothermal reactor, add a solvent and mix them evenly; Step 5: Set the reaction temperature of the hydrothermal reactor and keep it warm. After the reaction is completed and the temperature drops to 25°C, take out the solid-liquid mixture and filter it. The filtrate obtained is rich in furfural.
2. The method for efficiently preparing furfural by catalytic hydrolysis of cellulose according to claim 1, characterized in that: The carbon-based raw material includes combustible solid waste.
3. The method for efficiently preparing furfural by catalytic hydrolysis of cellulose according to claim 2, characterized in that: The combustible solid waste includes waste plastics, waste rubber and waste lignin.
4. The method for efficiently preparing furfural by catalytic hydrolysis of cellulose according to claim 1, characterized in that: In step 1, the metal chloride is ferric chloride, wherein the amount of the metal chloride is: the molar ratio of the metal element to the cellulose is x:1, wherein 0≤x≤1.
5. The method for efficiently preparing furfural by catalytic hydrolysis of cellulose according to claim 1, characterized in that: In the step 1, the heating rate of the tube furnace is 15°C / min-25°C / min; the carbonization time in the N2 atmosphere is 2h-4h; and the temperature of the water bath is 25°C-40°C.
6. The method for efficiently preparing furfural by catalytic hydrolysis of cellulose according to claim 1, characterized in that: In the step 2, the reaction kettle is placed in an oven for acidification for 10 hours to 12 hours.
7. The method for efficiently preparing furfural by catalytic hydrolysis of cellulose according to claim 1, characterized in that: In the step 3, the black solid material obtained by filtration is calcined at 500° C. to 600° C. for 3 h to 6 h.
8. The method for efficiently preparing furfural by catalytic hydrolysis of cellulose according to claim 1, characterized in that: In step 4, the mass ratio of catalyst to cellulose is m 催化剂 :m 纤维素 =x:1, where 0.5≤x≤4.
9. The method for efficiently preparing furfural by catalytic hydrolysis of cellulose according to claim 1, characterized in that: Features The solvent added in step 4 is a non-protonic polar compound.
10. The method for efficiently preparing furfural by catalytic hydrolysis of cellulose according to claim 1, characterized in that: In the step 5, the reaction temperature of the hydrothermal reactor is set to 150°C-210°C, the heating rate is 10°C / min-20°C / min, and the insulation time is 30min-180min.
Citation Information
Patent Citations
Method for preparing furfural by catalytic hydrolysis of lignocelluloses biomasses
CN103554067A
Loaded type carbon-based solid acid catalyst as well as preparation method and application thereof
CN106622285A
Method for producing furfural from lignocellulosic biomass material
US20110144359A1